2008
DOI: 10.1097/chi.0b013e31816c5c10
|View full text |Cite
|
Sign up to set email alerts
|

Observational Assessment of Preschool Disruptive Behavior, Part II: Validity of the Disruptive Behavior Diagnostic Observation Schedule (DB-DOS)

Abstract: The multidomain, multicontext approach of the DB-DOS is a valid method for direct assessment of preschool disruptive behavior. This approach shows promise for enhancing accurate identification of clinically significant disruptive behavior in young children and for characterizing subtypes in a manner that can directly inform etiological and intervention research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 31 publications
4
99
0
Order By: Relevance
“…3,16 Several investigators have also assessed predictive validity. Wakschlag and colleagues 6 found that 55% of their clinically enriched sample retained DBD status at one-year follow-up. Speltz and colleagues 20 assessed the 2-year stability of ODD and found that that the vast majority of children in their clinic-based sample (76%) continued to meet criteria for ODD diagnosis 2 years later.…”
Section: Validitymentioning
confidence: 98%
See 2 more Smart Citations
“…3,16 Several investigators have also assessed predictive validity. Wakschlag and colleagues 6 found that 55% of their clinically enriched sample retained DBD status at one-year follow-up. Speltz and colleagues 20 assessed the 2-year stability of ODD and found that that the vast majority of children in their clinic-based sample (76%) continued to meet criteria for ODD diagnosis 2 years later.…”
Section: Validitymentioning
confidence: 98%
“…We have suggested that accurate identification during this developmental period requires a developmentally specified approach to establish the critical features of behavior disorders that distinguish symptoms from the normative misbehavior of early childhood. 6,10 This developmentally specified approach would include elements such as identifying unique criterial features of behavior disorders in young children, establishing duration and symptom criteria cutoff points to generate maximally sensitive and specific thresholds, and defining symptom parameters in a manner that sharpens the typical: atypical distinction. In the following section, we apply a developmental lens to elucidate this approach.…”
Section: Dbds and Adhd: Applying A Developmental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that ADHD symptoms can be systematically elicited and reliably observed and quantified in preschoolers with externalizing behavior problems using the Disruptive Behavior Diagnostic Observation Schedule (DB-DOS) [4,5]. In this 1 h observation, the child's behavior is assessed in three interactional contexts: one parent and two examiner (engaged and non-engaged) contexts [24,25]. The DB-DOS was specifically designed to elicit high rates of clinically salient behavior in an efficient manner, in order to increase the likelihood that such variation will be observed within a standardized clinical assessment.…”
mentioning
confidence: 99%
“…Due to lack of language fluency, interviews are rarely administered to infants and preschoolers. Instead, observation or behavior rating methods have been used more frequently in examining overt aggression [10]. On the other hand, teachers' reports or peer nominations can be a better way to identify victims or bullies of relational aggression, given the fact that relational manipulation occurs in a less visible way [11].…”
Section: Introductionmentioning
confidence: 99%